Pelatihan dan Pendampingan Intepretasi Informasi Laporan Keuangan Menggunakan Aplikasi Sistem Informasi Pelaporan Keuangan Berbasis Jaringan Client-Server - Yusnaini; Arista Hakiki (Jurusan Akuntansi Fakultas Ekonomu Universitas Sriwijaya, 2024)
The purpose of this activity is to provide training and mentoring on interpreting financial report information using a client-server network-based financial reporting information system application at the employee cooperative of PT. Pusri. The benefit of this activity is to contribute to the development of cooperative businesses in Palembang, especially in interpreting and analyzing financial reports. The target audience of this activity includes all accounting and finance staff, as well as the management of PT. Pusri's employee cooperative in Palembang. The main output of this activity is a guide on how to interpret client-server-based financial reports, which can be used regularly and optimally by cooperative practitioners in Palembang, especially at Kopkar PT. Pusri Palembang. This activity will help cooperative practitioners understand the importance of accurate financial report interpretation for cooperatives, which is useful in showing the business results (profit/loss) to analyze the development of the business. By using a network-based web application, it will be easier and faster for MSME practitioners to create financial reports